2007
DOI: 10.1097/01.aids.0000304708.64294.3f
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of and barriers to voluntary HIV counselling and testing among adults in Guizhou province, China

Abstract: Education about HIV/AIDS and VCT needs to be improved, and levels of stigma and discrimination reduced, in order to enhance the uptake of VCT services, an essential step for the initiation of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
76
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 14 publications
17
76
3
Order By: Relevance
“…Most importantly, about two thirds of the respondents reported that they didn't consider themselves at risk and most of them were married. These findings concur with those reported from the study in China (Ma et al 2007) elsewhere in Tanzania (Maman et al, 2001). The later observed that fear of partners' reaction, decision-making and communication patterns between partners, and partners' attitudes towards HIV-1 testing were among the most important challenges to undertake HCT.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…Most importantly, about two thirds of the respondents reported that they didn't consider themselves at risk and most of them were married. These findings concur with those reported from the study in China (Ma et al 2007) elsewhere in Tanzania (Maman et al, 2001). The later observed that fear of partners' reaction, decision-making and communication patterns between partners, and partners' attitudes towards HIV-1 testing were among the most important challenges to undertake HCT.…”
supporting
confidence: 90%
“…It further showed that about two thirds of the adult population ever had HIV test done by the time this study was conducted. In a recent study in China, a much lower proportion (23%) of participants was of the opinion that there was no benefit of being tested (Ma et al 2007). The higher proportion of individuals who had correct understanding of HCT in our study is likely to have been contributed by a higher level of education among them.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…Unsafe commercial sex and unsafe homosexual sex are major drivers of the resurgent syphilis epidemic, 10 but there is ample data suggesting that neither sex workers nor homosexual men attend clinics in great numbers. 11,12 When these high-risk individuals do attend public clinics in China, there is often no record of their detailed sexual history, which is not in line with official guidelines. 13 There is no tradition of secondary case finding or partner notification in China (or in many low-income nations), so all related infections remain untreated.…”
Section: Current Syphilis Policymentioning
confidence: 99%
“…Low perception of risk, lack of knowledge, and the stigma associated with HIV represent significant barriers to testing (21)(22)(23), contributing to these rates.…”
Section: Introductionmentioning
confidence: 99%